Fenomena Sandwich Generation pada Era Modern di Kalangan Mahasiswa - Wicak, Widyawati Muktining; Hastuti, Maria Agatha Sri Widyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Sandwich generation or sandwich generation is a condition where someone is in a pinch like a sandwich, this sandwich generation is in a pinch in the family from their parents and also from other family members such as their younger siblings or older siblings, a condition where someone who becomes a sandwich generation must support two family members while he also has to support himself in terms of food, education, health and so on, this phenomenon has occurred a lot because of the inability of parents to be truly ready to take on their great responsibilities as parents, so that it has an impact on their children or even grandchildren and subsequent generations.